2019
DOI: 10.1007/s00382-019-05018-2
|View full text |Cite
|
Sign up to set email alerts
|

A new mathematical framework for atmospheric blocking events

Abstract: We use a simple yet Earth-like hemispheric atmospheric model to propose a new framework for the mathematical properties of blocking events. Using finite-time Lyapunov exponents, we show that the occurrence of blockings is associated with conditions featuring anomalously high instability. Longer-lived blockings are very rare and have typically higher instability. In the case of Atlantic blockings, predictability is especially reduced at the onset and decay of the blocking event, while a relative increase of pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 141 publications
(186 reference statements)
1
30
0
Order By: Relevance
“…Along these lines, using an idealised multi-scale system made up of coupled copies of the Lorenz 3-variables model, the authors of [50] demonstrate that weakly stable directions are needed in situations of strong nonlinear dynamics and intermittent error growth. Similarly, the authors of [39] have suggested that the variability in the number of unstable modes associated to unstable periodic orbits in a simple Earth system model, can explain the observed very different predictability of individual atmospheric blocking events, and have argued that DA must thus cautiously incorporate stable modes too.…”
Section: Resultsmentioning
confidence: 98%
“…Along these lines, using an idealised multi-scale system made up of coupled copies of the Lorenz 3-variables model, the authors of [50] demonstrate that weakly stable directions are needed in situations of strong nonlinear dynamics and intermittent error growth. Similarly, the authors of [39] have suggested that the variability in the number of unstable modes associated to unstable periodic orbits in a simple Earth system model, can explain the observed very different predictability of individual atmospheric blocking events, and have argued that DA must thus cautiously incorporate stable modes too.…”
Section: Resultsmentioning
confidence: 98%
“…Certain spatial features of the phases of this mode do present striking similarities to the blocked and zonal flows that appear not just as the two stable equilibria in the highly idealized model of Charney and DeVore (1979), but also as unstable, though long-lived, patterns in much more realistic models, like the three-level, quasigeostrophic (QG3) model originally formulated by Marshall and Molteni (1993). The latter model is still widely used to study the nonlinear dynamics of large-scale, midlatitude atmospheric flows (e.g., Kondrashov et al, 2004;Lucarini and Gritsun, 2020).…”
Section: Atmospheric Low-frequency Variabilitymentioning
confidence: 84%
“…This coarse-graining of the LFV's phase space and Markov chain representation of the dynamics continues to inform current efforts at understanding what atmospheric phenomena can be predicted beyond 10-15 days and how. Recently, analyses based on dynamical systems theory have associated blocked flow configurations with higher instability of the atmosphere as a whole (Faranda et al, 2017;Lucarini and Gritsun, 2020;Schubert and Lucarini, 2016), as predicted by Legras and Ghil (1985).…”
Section: Atmospheric Variability In Mid-latitudesmentioning
confidence: 98%
See 1 more Smart Citation
“…More recently methods from dynamical systems theory have been employed. In particular, covariant Lyapunov vectors and unstable periodic orbits were shown to capture blocking events [43,28]. More closely related to our approach of DMD, methods based on the transfer operator, the formal L 2 -adjoint of the Koopman operator, and the behaviour of its point spectrum were used to study transitions to individual blocking event [44].…”
Section: Detecting the Inter-decadal Changes In The North Atlantic Osmentioning
confidence: 99%